Development of CO2 Hub-Clustering Management in The South Sumatra Basin - Fanata Y Nugraha; M. Firdaus Al Hakim; Brian Tony; Damar Nandiwardhana; Steven Chandra (Scientific Contributions Oil and Gas, 2024)
The escalating urgency of mitigating climate change demands immediate and effective strategies, with Carbon Capture and Storage (CCS) emerging as a pivotal solution. This scientific study presents a systematic and quantitative approach to selecting carbon dioxide (CO2) storage sites, focusing on the petrochemical industry in South Sumatra as the CO2 source, with annual emissions reaching 3.5 MtCO2. A comprehensive screening process was executed, employing 14 distinct criteria, each assigned a weighted score, to ensure the inclusion of technically feasible CO2 capture and storage options. Notably, the emphasis on Subsurface Data Analysis, encompassing vital factors such as storage reservoirs, boundary zones, traps, potential injectivity, prospective storage resources, and existing seismic data, served as a cornerstone in enhancing the robustness of our assessments. The research successfully identifies 15 CO2 storage fields, with a total storage capacity of up to 475 MtCO2. This quantitative evidence underscores the substantial potential for large-scale CO2 storage within the study area. Furthermore, considering spatial dynamics, with two distinct scenarios within a 100 km and 200 km radius of CO2 emission sources, provided precise quantitative insights into the geographical distribution of these storage sites relative to emission sources. It is crucial to note that optimizing pipeline infrastructure and utilizing existing Right of Way (ROW) were quantitatively validated as cost-effective measures for CO2 distribution, which is especially significant given the urgency of implementing CCS. Spatial calculations supported the proposal of a 600-kilometer pipeline route, demonstrating the quantitative feasibility of leveraging existing infrastructure to facilitate extensive CO2 management. This research could help in understanding large-scale CO2 storage potential and provides valuable insights for CCS policy and business development in South Sumatra